Activation and Retention: A Magnetic Resonance Probe for the Detection of Acute Thrombosis1. (11th December 2013) - Loving, Galen S.; Caravan, Peter
Abstract Blood‐clot formation that results in the complete occlusion of a blood vessel (thrombosis) often leads to serious life‐threatening events, such as strokes and heart attacks. As the composition of a thrombus changes as it matures, new imaging methods that are capable of distinguishing new clots from old clots may yield important diagnostic and prognostic information. To address this need, an activatable magnetic resonance (MR) probe that is responsive to a key biochemical process associated with recently formed clots has been developed.